Severe Infantile Blount’s Disease in Kumasi, Ghana: A Case Report - Dominic Konadu-Yeboah; Peter Konadu; Ampem Darkwa; Banahene; Adu-Osei (Journal of Preventive Medicine And Care, 2019)
Blount’s disease, also known as tibia vara, is a developmental disorder involving the posteromedial proximal tibial physis resulting in progressive varus, procurvatum and internal torsion of the affected tibia 1. The condition was first published by Blount in 1973 2. The aetiology of this disease is unkown. However, associations exist between blount’s disease and the Afro-Caribbean race, early age of walking and obesity 34. Furthermore, genetic predisposition has been postulated as well as mechanical loading of the physis 456. Affected children are usually overweight and start walking early. It is bilateral in 80% of cases 7.
Keywords: Infantile Blount’s Disease